SHARE

TWEET

# Untitled

a guest
Sep 23rd, 2016
172
Never

**Not a member of Pastebin yet?**

**, it unlocks many cool features!**

__Sign Up__- #1
- Let x, y be given. We show that x + y = y + x.
- Observe 0 = (x + y) + (x + y). Add (y + x) from the left on both sides to get y + x = (y + x) + (x + y) + (x + y)
- = (y + (x + x) + y) + (x + y) = (y + y) + (x + y) = x + y. Q.E.D.
- #2
- Let x, y be given such that 0 = x + y. Add x from the left on both sides to get x = (x + x) + y = y. Q.E.D.

RAW Paste Data

We use cookies for various purposes including analytics. By continuing to use Pastebin, you agree to our use of cookies as described in the Cookies Policy.